PENGARUH PENGGUNAAN METODE COURSE REVIEW HORAY TERHADAP HASIL BELAJAR IPS KELAS VSD - Savitriani, Nita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of this reasearch is to analyze effect of the application ofmethod course review horay student learning outcomes in Social Science Learningon the 5th Â grade of Elementary School 11 Pontianak City. Research methods that used is experimental method with Quasi Experimental Design, with Nonequivalent Control Group Design.Population in this research is all of 5th grade of two classes from class VA to class VBwith total 51 students. The sample of this research are class VA consist of 27 students (experiment) and class VB consist of 24 students (control). The average learning outcomes of final test class VAis 74,33and class VBis 64,50 gained tarithmetic (3,964)>ttable Î±=5% (2,001), then Ha acceptable. So, the conclution is there are two average significant differences learning outcomes of students, among students group that teach with apply without methods of course review horayand students group that teach with apply ofmethod course review horay approach of 5th grade of Elementary School 11 Pontianak City. The value of effect size is 0,79 with are criteria medium, this case mean applying method course review horay approach toSocial Science Learninggive are effect for learning outcomes of 5th grade of Elementary School11Pontianak City. Â Keywords : Course Review Horay, Learning Outcomes, Social Science.